PENGARUH STRUKTUR MODAL, LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Dedi Karmana (LPPM POLITEKNIK LP3I BANDUNG, 2015)
The purpose of this study to determine the effect of the independent variables simultaneously or partially on the variable Dividend Payout Ratio (DPR) and how big contribution. This is so that the company knows how dividend policy can be implemented properly. The results of this study showed all the independent variables simultaneously have a significant effect on dividend policy. Partially only variable Debt to Equity Ratio (DER), Current Ratio (CR) and Return on Assets (ROA), which has a significant effect on Dividend Payout Ratio (DPR) and the variation of all the independent variables used to explain 28.40% while the remaining variables Dividend Policy 71,60% is explained by other variables outside the model.